Seed priming enhances seed germination and plant growth in four neglected cultivars of Capsicum annuum L. - Granata,Angelo; Capozzi,Fiore; Gaglione,Anna; Riccardi,Riccardo; Spigno,Patrizia; Giordano,Simonetta; Sorrentino,Maria Cristina; Spagnuolo,Valeria (PeerJ, 2024)
Priming is basically a water-based technique inducing controlled seed rehydration to trigger the metabolic processes normally activated during the early phase of germination. It is regarded as an ecofriendly approach alternative to fertilizers in traditional agriculture, but also a method to synchronize off-field crops and resume stored seeds, improving vigor, and allowing for a rapid, uniform seedling emergence. In this work we tested several methods of seed priming (i.e., hydro-priming, halopriming by KNO3, and acid priming with HCl) in four ancient and neglected cultivars of Capsicum annuum L., a crop species belonging to Solanaceae family cultivated worldwide. We followed germination performance, seedling growth and selected morphological traits, antioxidant production in the leaves, and protein content of the seeds. Apart from acid priming, which inhibited root emergence, both hydropriming and halopriming decreased the mean germination time in all cultivars. The best treatments were KNO3 6% for 96 h > KNO3 4% for 48 h > hydropriming for 24 h. In particular, KNO3 6% for 96 h in all four cultivars significantly increased plant growth, simple vigor index, development germination index, leaf antioxidant concentration and protein content in the seeds, in comparison to control and other priming treatments, indicating the prompt activation of pre-germinative processes.
Keywords: Sweet pepper; Germination performance; Hydropriming; Halopriming; Seed vigor index; Development germination index